2007
DOI: 10.4141/a06-082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grain source, silage level, and slaughter weight endpoint on growth performance, carcass characteristics, and meat quality in Angus and Charolais steers

Abstract: 2007. Effects of grain source, silage level, and slaughter weight endpoint on growth performance, carcass characteristics, and meat quality in Angus and Charolais steers. Can. J. Anim. Sci. 87: 167-180. Two growth performance trials were conducted to evaluate the effects of grain source (corn vs. barley), corn silage level (15 vs. 50%) and body weight (BW) at slaughter on growth performance, carcass characteristics, and beef quality. Gains were greater (P < 0.01) feeding corn vs. barley to Angus cattle slaught… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
(78 reference statements)
3
10
2
Order By: Relevance
“…However, apart from marbling score, the proportions of moisture, protein and fat in the Longissimus dorsi muscle were not significantly different in the present study. Our results are in agreement with several studies over the past decade (Miller et al, 1996;Boles et al, 2005;Koenig and Beauchemin, 2005;McEwen et al, 2007), which found no differences in WarnerBratzler shear force measurements, and taste panel evaluations for tenderness, juiciness, and flavour when comparing beef from cattle finished on maize vs barley. Fiems et al (1999) also found that the proportion of rumen degradable starch in the diet had no effects on the proportions of moisture, protein and fat in the Longissimus thoracis muscle.…”
Section: Physical and Chemical Characteristics Of Longissimus Dorsi Msupporting
confidence: 83%
See 2 more Smart Citations
“…However, apart from marbling score, the proportions of moisture, protein and fat in the Longissimus dorsi muscle were not significantly different in the present study. Our results are in agreement with several studies over the past decade (Miller et al, 1996;Boles et al, 2005;Koenig and Beauchemin, 2005;McEwen et al, 2007), which found no differences in WarnerBratzler shear force measurements, and taste panel evaluations for tenderness, juiciness, and flavour when comparing beef from cattle finished on maize vs barley. Fiems et al (1999) also found that the proportion of rumen degradable starch in the diet had no effects on the proportions of moisture, protein and fat in the Longissimus thoracis muscle.…”
Section: Physical and Chemical Characteristics Of Longissimus Dorsi Msupporting
confidence: 83%
“…The body weight at post-weaning was greatest in calves fed a maize diet followed by those fed a wheat diet and then in those on barley and oat diets, with the differences being ascribed to differences between the cereal sources in rumen starch degradability (Khan et al, 2007). McEwen et al (2007) reported that maize-fed steers grew faster than those fed barley and suggested that differences in gain due to grain source may be due to the higher net energy values of maize vs barley. Also Tiffany and Spears (2005) attributed greater gains and better feed conversion for maize-vs barley-fed steers to lower ME in barley diets due to higher NDF concentrations.…”
Section: Growth Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The concentrate proportion in experimental diets did not affect ADG of Brahman crossbred calves, which are consistent with the results reported by McEwen [21,32] in beef steers fed on iso-nitrogenous diets of 40%-100% concentrate or McEwen and Mandell [8] in Angus steers between 70% and 35% corn level in diet. Helal et al [33] reported similar ADG (941-1,017 g) in buffalo calves fed with diets of varied concentrate levels (70%, 85% and 100%).…”
Section: Lwg and Feed Conversion Efficiencysupporting
confidence: 90%
“…However, a trend towards higher gain costs was observed as grain level increased. In a trial of four iso-nitrogenous diets, cost estimates were greater (1 kg of gain) for cattle fed with the high grain or concentrate diet, and as grain levels increased, cost of gain estimates also increased [8]. Therefore, it is quite necessary to evaluate a range of C:R ratio in iso-nitrogenous and iso-caloric diets for feedlot cattle.…”
mentioning
confidence: 99%